PELAKSANAAN PENDIDIKAN MADRASAH DINIYAH DI KOTA SERANG - Anis Fauzi; Cecep Nikmatullah (Jurnal Pendidikan dan Kebudayaan, 2016)
The purpose of this research were 1) To assess the policy of islamic education according to Local Regulation of Serang City Number 1 Year 2010 and Mayor of Serang City Regulation Number 17 Year 2013; 2) To assess the requirements to continue education to general junior secondary education/Islamic junior secondary education (SMP/MTs) in the realization of Regulation of Serang City number 1 year 2010; and 3) To determine supporting and inhibiting factors for the implementation of Islamic basic education in Serang City. This study used qualitative research method. Data were collected from the observation, interview, and documentation. From the analysis it is found that 1) The policy of compulsory of Islamic basic education is reserved for every muslim citizen who will continue to general junior secondary education /islamic junior secondary school; 2) Every muslim students aged 6 to 12 years who will continue their education to the next level has to possess certificate of Islamic education completion; 3) Support for the implementation of the regulation is gained from various group of people. However, the less socialized regulation inhibits people to be well informed about the legal certainty for the regulation. Thus, the implementation of the Islamic education regulation requires reconsideration for the formulation of strategic objectives and the improvement of the education quality to adjust to the more complex of culture shift. ABSTRAKMasalah pokok dalam kajian ini adalah faktor apa yang mendukung dan menghambat implementasi Perda tentang Penyelenggaraan Wajib Belajar Pendidikan Diniyah di SMP/MTs. Tujuan penelitian ini yaitu untuk (1) mengetahui kebijakan Pendidikan Islam di madrasah diniyah menurut Perda Kota Serang; (2) mengetahui implementasi SMP/MTs dalam merealisasikan Perda Diniyah; serta (3) mengetahui faktor pendukung dan penghambat implementasi pendidikan madrasah diniyah di Kota Serang. Studi ini menggunakan metode penelitian kualitatif. Data-data penelitian dikumpulkan dari hasil observasi, wawancara, dan dokumentasi. Objek penelitiannya yaitu: pertama, Perda Kota Serang tentang Wajib Belajar Pendidikan Diniyah. Kedua, Perwal Kota Serang tentang Penyelenggaraan Wajib Belajar Pendidikan Diniyah di Kota Serang. Hasil analisis data diperoleh temuan bahwa: (1) kebijakan wajib belajar pendidikan diniyah diperuntukkan bagi setiap warga negara yang akan menempuh jenjang pendidikan SLTP; (2) adanya sosialisasi perda diniyah oleh pemerintah Kota Serang; (3) faktor pendukung implementasi Perda Diniyah di Kota Serang yaitu dukungan masyarakat, ilmuwan, akademisi, dan tokoh masyarakat Kota Serang. Kesimpulannya adalah pelaksanaan Perda Diniyah membutuhkan peninjauan kembali mengenai rumusan tujuan strategis dan pembenahan mutu pendidikan untuk penyesuaian tuntutan sejalan dengan perkembangan budaya bangsa yang semakin kompleks.